2023
DOI: 10.2147/dmso.s395923
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Red Cell Distribution Width to Glucose Metabolism and Adverse Long-Term Prognosis in Patients with Acute Coronary Syndrome

Abstract: Introduction Red cell distribution width (RDW) reflects the heterogeneity of red blood cell size. However, few studies examined whether RDW is related to glucose metabolism indices, such as fasting blood glucose (FBG) and hemoglobin A1c (HbA1c), diabetic mellitus (DM) state or long-term outcomes of acute coronary syndrome (ACS) patients. Methods and Results A total of 448 consecutive patients with ACS were enrolled in this study. All patients were followed up for major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This difference in red blood cell size ultimately increases RDW. Hyperglycemia, insulin resistance, and hyperinsulinemia, which are the main clinical abnormalities in DM, promote inflammation, oxidative stress, and other pathophysiological abnormalities ( Ke Xiong et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…This difference in red blood cell size ultimately increases RDW. Hyperglycemia, insulin resistance, and hyperinsulinemia, which are the main clinical abnormalities in DM, promote inflammation, oxidative stress, and other pathophysiological abnormalities ( Ke Xiong et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…20 Increased RDW has also been found to be associated with increased major adverse cardiovascular events (MACEs) in patients with ACS. 21 Meanwhile, lower RDW has been linked to a lower risk of cardiovascular mortality and MACEs following ACS. 19 Our study demonstrated increased levels of total and differential leucocytes (Table 1) and HbA1c was also found to be significantly positively correlated with leucocytes and segmented neutrophils (Table 2).…”
Section: Discussionmentioning
confidence: 99%